Negotiating Environmental Agreements under Ratification Uncertainty - Sonja Köke; Andreas Lange (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In this paper we analyze how rati cation uncertainty impacts the optimal terms of international environmental agreements (IEAs). We relax the frequent assumption of countries as unitary actors by modeling the rati cation stage through uncertain preferences of a ratifying agent (e.g. the pivotal voter). With this, we combine the literature on IEAs with the one on two-level games of rati cation. We nd that rati cation uncertainty reduces both the strength of the commitment as well as the participation threshold, thereby a ecting intensive as well as extensive margins of expected international cooperation. Similar comparative statics arise under uncertainty when pivotal voters' and negotiators' preferences diverge. This is a rst step towards linking individual voters' preferences to the outcome of IEAs.
Keywords: Q54; C72; H41; 330